2009
DOI: 10.1080/09553000902954538
|View full text |Cite
|
Sign up to set email alerts
|

The electric field is a sufficient physical determinant of the human magnetic sense

Abstract: The evoked potentials described here, as well as those observed previously in response to magnetic stimuli, were probably triggered by the induced electric field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…However we previously presented evidence that the coupling between environmental EMFs and brain tissue was mediated by negatively charged oligosaccharide side chains bound to the gate of an ion channel whose gating characteristics were affected by the electric field induced in the tissue by the magnetic component of the environmental EMF [28].…”
Section: Discussionmentioning
confidence: 99%
“…However we previously presented evidence that the coupling between environmental EMFs and brain tissue was mediated by negatively charged oligosaccharide side chains bound to the gate of an ion channel whose gating characteristics were affected by the electric field induced in the tissue by the magnetic component of the environmental EMF [28].…”
Section: Discussionmentioning
confidence: 99%
“…Further efforts to establish the true magneto sensitivity of cryptochrome in plants are required. The other three models include: (3) electromagnetic induction in a) highly sensitive electric sensors (ampullae of Lorenzini) in Elasmobranchii fish [Kalmijn, ; Paulin, ] or in b) potentially specialized force receptors where negatively charged oligosaccharide side chains are covalently bound to ion channels in plasma membrane [Carrubba et al, ; Marino et al, ]; (4) the ion cyclotron resonance model that could affect ion transport rates and binding of ions to receptors under the influence of the GMF [Liboff, ; Liboff, ]; and (5) quantum coherence that has been found [Fleming et al, ; Lambert et al, ] or postulated in living organisms such as the coherent domains of water molecules proposed by Del Giudice et al []. It has also been shown that magnetic fields can change the intracellular level of Ca 2+ ions and can influence calmodulin‐dependent pathways that control several different biochemical pathways in plants [Funk et al, ; Pazur and Rassadina, ; Markov, ].…”
Section: Discussionmentioning
confidence: 99%
“…Деякі негативні наслідки для здоров'я людини, які можуть бути спричинені тими чи іншими частотами електромагнітного спектру, наведено в роботі [2], де показано взаємозв'язок між частотами електромагнітного поля і типом індукованого стресу або пошкодження, зокрема, індивідуальними функціональними реакціями та поведінкою. Так, поля з частотами 10 4 -10 8 Гц можуть спричиняти психологічні розлади та викликати психосоматичні реакції [3][4][5][6][7][8], а поля з частотами 10 8 -10 12 Гц викликають неврологічні реакції та розлади сну та поведінки [9]. В діапазоні 10 12 -10 18 Гц (світловий діапазон) вплив електромагнітних полів може викликати термічно індуковані біохімічні зміни, зокрема, підвищену експресію білків теплового шоку, експресію вітамінів (групи D) та мелатоніну, циркадну експресію гормонів, а також, перебудову клітинного циклу в шкірі, канцерогенні і мутагенні відповіді [10][11][12][13].…”
Section: результати дослідженняunclassified